2023
DOI: 10.3389/fmicb.2023.1131953
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-dependent influence of prebiotics on the resilience of infant gut microbiota to amoxicillin/clavulanate perturbation in an in vitro colon model

Abstract: Antibiotic exposure disturbs the developing infant gut microbiota. The capacity of the gut microbiota to recover from this disturbance (resilience) depends on the type of antibiotic. In this study, infant gut microbiota was exposed to a combination of amoxicillin and clavulanate (amoxicillin/clavulanate) in an in vitro colon model (TIM-2) with fecal-derived microbiota from 1-month-old (1-M; a mixed-taxa community type) as well as 3-month-old (3-M; Bifidobacterium dominated community type) breastfed infants. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…Faecal samples of infants were collected within the Baby Carbs Study as briefly reported by Endika and co-authors. 47 Faecal slurries of two individual adults, two weaning infants at 6 months old and the same two infants at 9-10 months old were prepared as described above, snap-frozen in liquid nitrogen and stored at −80 °C prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Faecal samples of infants were collected within the Baby Carbs Study as briefly reported by Endika and co-authors. 47 Faecal slurries of two individual adults, two weaning infants at 6 months old and the same two infants at 9-10 months old were prepared as described above, snap-frozen in liquid nitrogen and stored at −80 °C prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The V4 region of the 16S rRNA gene was amplified in duplicate using barcoded 515F [26]-806R [27] primers. The full description of the PCR steps has been provided in a previous study [28]. 25 or 30 PCR cycles were used for fecal or milk samples, respectively.…”
Section: Microbiota Analysismentioning
confidence: 99%
“…Studies have found that adding prebiotics early in life can help infants establish a healthy gut microbiome [17]. At the same time, the direct or combined use of prebiotics in the treatment of infant diarrhea is more effective than the use of antibiotics alone and can effectively prevent intestinal disorders caused by antibiotics, etc., which also suggests that the use of prebiotics to correct intestinal microecological disorders may become an important measure to improve antibiotic treatment [18]. However, it is currently unclear whether GOS alleviates intestinal barrier damage by promoting probiotic proliferation, and similarly, few studies have investigated the effect of GOS on preventing and recovering microbiota after ampicillin-induced microbiota disruption.…”
Section: Introductionmentioning
confidence: 99%